PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW DAN TIPE NHT TERHADAP HASIL BELAJAR SISWA - Fransiskus Hardin; Edy Widayat; Yuli Listiana (Jurnal Riset Pembelajaran Matematika, 2020)
The purpose of this study was a) to see if there was an application of the Jigsaw-type cooperative learning model with NHT on the learning outcomes of class VII students of SMP IPIEMS Surabaya. b) To see whether there is an effect of using the Jigsaw and NHT cooperative learning models on the learning outcomes of seventh grade students of SMP IPIEMS Surabaya. This study used a quantitative approach and the type of experimental research was using true experimental design with the pretest-posttest control group design. The statistical test used is the sample t test and multiple linear regression. The results showed: a) there was no application of the jigsaw cooperative learning model with the NHT type on student learning outcomes, b) there was a significant effect on the application of the jigsaw and NHT cooperative learning model.